Upaya Meningkatkan Hasil Belajar Matematika Materi Bangun Ruang Sisi Datar Melalui Model Direct Instruction Dengan Menggunakan Multimedia Siswa Kelas VIII-C SMP Negeri 1 Candi Sidoarjo - Zaelani, Mansur (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study uses Classroom Action Research (CAR). The subjects in this study were class VIII-C students at SMP Negeri 1 Candi Sidoarjo with a total of 40 students. The research data were obtained from the Observation Method and Test Method and data analysis techniques using student activity analysis and conceptual understanding. The results of the study show that learning by applying direct instruction (Direct Instruction) with multimedia, namely: 1) Improving student mathematics learning outcomes and a positive impact on improving student learning achievement, 2) Improving teacher performance as a whole has met the good criteria. The increase in the percentage of students' learning interest from Pre-cycle to Cycle I was 9.04 or had an increase percentage of 20.41%. While the increase in the percentage of interest in learning from Cycle I to Cycle II was 12.86 or had an increase percentage of 24.11%.